INSTITUTIONAL STRUCTURING POLICY IN SUSTAINABLE DEVELOPMENT IN THE BORDER REGION - Asri, Syachrumsyah (Jurnal Aplikasi Manajemen, 2018)
Coordination of the program border area development is still sporadic, as implemented by many departments at the central level. While it’s still the sectoral nature of the program implementation according to the interests of each sector. The purpose of this research is to know the characteristics of the border region and community development in the region, as well as to draw up a strategy and policy development of the border region. This research concluded that there should be an established government institutions and directly responsible border management from conducting the central level in the form of Separate ministry, namely the Minister for the management of the State border of the Republic of Indonesia whose has the many devices, there are a central Government, Province, Regency/City, subdistrict until getting to the villages on the border.